2018
DOI: 10.1109/lpt.2018.2821191
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Transmission Performance Using Backward-Propagated Broadband ASE Pump

Abstract: Abstract-We propose a novel first order incoherent broadband ASE pump which can be used as a seed pump in dual order backward-pumped distributed Raman amplification. Using this broadband ASE pump mitigates the RIN transfer from the backward-propagated second order pump to the signal, and extends the reach of 10 × 120 Gb/s DP-QPSK WDM transmission to 7915 km, giving a minimum of 12% (833 km) increase, compared with using low RIN semiconductor laser diode and random distributed feedback (DFB) fiber laser.Index T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In Reference [34], the authors presented a sixth-order Raman pump configuration. However, the commonly used Raman schemes are based on first-order and second-order Raman amplifiers which have relatively configurations, higher pump-signal conversion efficiency and consequently lower cost [35][36][37][38][39][40][41][42][43]. Using only forward Raman pumping is generally not feasible for transmission systems because firstly, it introduces significant RIN-related penalty to the transmitted signal from the pump, and secondly the signal suffers high fiber nonlinearity due to high signal power near the input sections of the transmission span [35][36][37][38][39][40][41][42][43].…”
Section: Optimized Distributed Raman Amplification Design Over Single Fiber Spanmentioning
confidence: 99%
See 2 more Smart Citations
“…In Reference [34], the authors presented a sixth-order Raman pump configuration. However, the commonly used Raman schemes are based on first-order and second-order Raman amplifiers which have relatively configurations, higher pump-signal conversion efficiency and consequently lower cost [35][36][37][38][39][40][41][42][43]. Using only forward Raman pumping is generally not feasible for transmission systems because firstly, it introduces significant RIN-related penalty to the transmitted signal from the pump, and secondly the signal suffers high fiber nonlinearity due to high signal power near the input sections of the transmission span [35][36][37][38][39][40][41][42][43].…”
Section: Optimized Distributed Raman Amplification Design Over Single Fiber Spanmentioning
confidence: 99%
“…However, the commonly used Raman schemes are based on first-order and second-order Raman amplifiers which have relatively configurations, higher pump-signal conversion efficiency and consequently lower cost [35][36][37][38][39][40][41][42][43]. Using only forward Raman pumping is generally not feasible for transmission systems because firstly, it introduces significant RIN-related penalty to the transmitted signal from the pump, and secondly the signal suffers high fiber nonlinearity due to high signal power near the input sections of the transmission span [35][36][37][38][39][40][41][42][43]. Therefore, in this paper, we mainly focus on the designs of first-order and second-order distributed Raman amplification schemes using backward or bidirectional pumping which requires the RIN penalty mitigation technique.…”
Section: Optimized Distributed Raman Amplification Design Over Single Fiber Spanmentioning
confidence: 99%
See 1 more Smart Citation
“…But the experiment demonstrated that this scheme can provide better balance between amplified spontaneous emission (ASE) noise and nonlinear effects, which results in better transmission performance [10][11][12]. In addition to them, it is shown in recent studies that DRAs using broadband optical pump exhibit superior RIN performance over conventional DRAs including backward pumping and random fiber laser [13]. The broadband optical pump is generated by ASE of second order pump in the fiber with high Raman gain coefficient, and then the broadband optical pump is launched into transmission fiber to amplify the signal.…”
Section: Introductionmentioning
confidence: 99%